An institutional theory perspective of business continuity planning for purchasing and supply management - Zsidisin, G. A.; Melnyk, S. A.; Ragatz, G. L. (International journal of production research, 2005)
Supply chains are increasingly susceptible to unplanned, unanticipated disruptions. With the implementation of the practices of lean systems, total quality management (TQM), time-based competition and other supply chain improvement initiatives, managers now realize that their supply chains are fragile, particularly to environmental disruptions outside their control. As a result of recent events including 11 September 2001, a system is now emerging in purchasing to manage supply risk characterised as having a very low probability of occurrence, difficult to predict, and with a potentially catastrophic impact on the organization. This paper presents case study research findings examining how and why firms create business continuity plans to manage this risk. Propositions are then presented from an institutional theory perspective to examine how various isomorphic pressures result in firms having similar risk management practices embedded in their supply management practices over time.